Sistem Pendukung Keputusan Kesehatan Mental Mahasiswa Menggunakan Metode SAW Berbasis Web - Azra Aaliyah Seisha Sybille; Ida Bagus Gede Dwidasmara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
This study presents the development of a web-based decision support system (DSS) utilizing the Simple Additive Weighting (SAW) method to evaluate student mental health based on the SRQ- 20 questionnaire. Data collected via the questionnaire were processed using SAW to determine relative criterion weights. The DSS aims to assist educational institutions in supporting student mental well-being by identifying those needing attention. Results reveal that out of 10 sampled students, 8 experienced mental health distress. The SAW method effectively ranked students based on mental health conditions, offering insights for intervention strategies. The study concludes that the implementation of SAW in the DSS proved effective in identifying mental health concerns among students, highlighting the importance of proactive measures in supporting their well-being within academic settings. Further research may explore alternative methods to enhance decision-making processes regarding student mental health.